The impact of intraday markets on the market value of flexibility: Decomposing effects on profile and the imbalance costs - Christian Pape (University of Duisburg-Essen, House of Energy Markets & Finance, 2017)
An increasing share of variable renewable energy sources (VREs) basically affects the electricity price formation in two ways: (1) The so-called merit order effect tends to lower the base price level and challenges conventional plants to remain profitable. (2) Due to the variable nature of renewable energy infeed, the shortterm demand for flexibility increases and changes the volatility of electricity prices. The more variable prices offer opportunities for controllable electricity producers (CEPs) to provide up- and down-ramping flexibility to increase their revenues. In contrast, the VREs with high degrees of simultaneity tend to pay for this flexibility in the electricity spot market to reduce their imbalance exposure. The intraday market (IDM) for electricity has gained importance for the market value of different technologies lately and continues to expand due to the increasing efforts to balance within-day deviation from day-ahead schedules. This article presents a combination and extension of two existing models to capture the peculiarities of the intraday price formation and to analyse the impact of the IDM on the market value of VREs and CEPs. Doing so, the paper suggests an adjustment of the classical market value factor metric and to go beyond classical day-ahead market (DAM) information. The article shows that market value factors (MVFs) can be stabilized if the IDM delivers "marketbased" price signals for the costs of flexibility, that are sufficient to activate flexibilities prior to the usually more expensive imbalance mechanism (IBM). Yet, the MVFs from single VRE technologies will worsen if their market share is high enough to outweigh forecast errors from other technologies and if they become a permanent price maker in the IDM and the IBM.
Keywords: Q47; N74; 330; intraday markets; imbalance mechanism; market value; renewable energy